Working with families affected by mental distress: stakeholders' perceptions of mental health nurses educational needs - Keogh, Brian; Skärsäter, Ingela; Doyle, Luoise; Ellilä, Heikki; Jormfeldt, Henrika; Lahti, Mari; Higgins, Agnes; Meade, Oonagh; Sitvast, Jan; Stickley, Theodore; Kilkku, Nina (Informa Healthcare, 2017)
Family and informal caregivers provide a substantial amount of care and support to people who experience mental health problems. The aim of this study was to explore mental health nurses’, students’ and service users’ perceptions of the knowledge, skills and attitudes that are required by mental health nurses to work with families and carers using a qualitative methodology. Three themes emerged from the data: Knowledge of the family and how mental distress affects the family; Working with the family – support and education and Valuing the role of the family. The three themes demonstrate the complexity of preparing mental health nurses to work with families and carers and the paper offers recommendations about how this might be achieved.